Development of municipal-private partnership in the system of municipal crediting of Ukraine - Palokha, Olga (Technology audit and production reserves, 2018)
The object of research is the processes of formation and development of municipal-private partnership (MPP) in the system of communal lending in Ukraine. One of the most problematic places of the object of study is the lack of a unified definition of MPP in the scientific economic literature and current legislation. In the course of the study, general scientific and special methods are used, namely: abstract-logical to generalize the theoretical foundations of the emergence and development of MPP; analysis, synthesis, logical generalization to substantiate the prerequisites for development, the subject-objective characteristics of MPP, the means of increasing the effectiveness of such a partnership. Systematization of the conceptual and categorical apparatus with respect to the definition of the MPP essence allows to conclude that there is no single definition in the scientific literature. The author has provided his own MPP interpretation as a tool to ensure the development of long-term mutually beneficial cooperation of local governments with business structures and the public. With the help of MPP, a policy of regional and municipal socio-economic development is being implemented, and infrastructure and other projects that are socially important for the development of territorial units are co-financed. A systematic analysis of the problems of the development of small private entrepreneurship in Ukraine allowed to justify the direction of their elimination. The obtained results allow to determine the specific features of the MPP and its distinctive features from the state-private partnership (SPP). It is established that attracting private investors requires the development of an appropriate regulatory framework, restoring confidence in the instruments of local loans and the activities of local governments. To do this, it is necessary to ensure the openness and transparency of the MPP implementation projects by creating online platforms through which private investors can receive the necessary information. The construction of the scheme of the constituent elements of the MPP functioning allows to establish the subject-object composition, to determine the prerequisites for the development of such a partnership and its effectiveness. Thanks to this, it is possible to obtain a budgetary, social, environmental effect at the level of administrative-territorial units and the development of a system of communal lending in Ukraine.